Urgensi Epistemologi Islam bagi Setiap Penuntut Ilmu - Pranoto Effendi (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The dominance of western civilization has extended to the epistemological aspect of science which places great emphasis on the physical aspects of science. Meanwhile, in the past, Muslim scientists have passed down a complete legacy and explained epistemology in accordance with the principles and teachings of the Islamic religion. This article aims to explain the urgency of Islamic epistemology for those who wish to study by providing a descriptive and analytical explanation. Only a correct epistemology that is in accordance with Islamic teachings can lead students of science to the essence of science, namely knowledge as it really is and provide spiritual satisfaction and happiness.